"Trade‐Off" Hidden in Condensed State Solvation: Multiradiative Channels Design for Highly Efficient Solution‐Processed Purely Organic Electroluminescence at High Brightness. (8th December 2017) - Cai, Xinyi; Chen, Dongjun; Gao, Kuo; Gan, Lin; Yin, Qingwu; Qiao, Zhenyang; Chen, Zijun; Jiang, Xiaofang; Su, Shi‐Jian
Abstract: Actualizing highly efficient solution‐processed thermally activated delayed fluorescent (TADF) organic light‐emitting diodes (OLEDs) at high brightness becomes significant to the popularization of purely organic electroluminescence. Herein, a highly soluble emitter benzene‐1, 3, 5‐triyltris((4‐(9, 9‐dimethylacridin‐10(9 H )‐yl)phenyl)methanone was developed, yielding high delayed fluorescence rate ( k TADF > 10 5 s −1 ) ascribed to the multitransition channels and tiny singlet–triplet splitting energy (Δ E ST ≈ 32.7 meV). The triplet locally excited state is 0.38 eV above the lowest triplet charge‐transfer state, assuring a solely thermal equilibrium route for reverse intersystem crossing. Condensed state solvation effect unveils a hidden "trade‐off": the reverse upconversion and triplet concentration quenching processes can be promoted but with a reduced radiative rate from the increased dopant concentration and the more polarized surroundings. Striking a delicate balance, corresponding vacuum‐evaporated and solution‐processed TADF‐OLEDs realized maximum external quantum efficiencies (EQEs) of ≈26% and ≈22% with extremely suppressed efficiency roll‐off. Notably, the wet‐processed one achieves to date the highest EQEs of 20.7%, 18.5%, 17.1%, and 13.6%, among its counterparts at the luminance of 1000, 3000, 5000, and 10 000 cd m −2, respectively. Abstract : Hidden "trade‐off" among highly radiative rate, rapid reverse upconversion, and suppressed concentration quenching is reached by condensed state solvation. With multitransition channels design for thermally activated delayed fluorescence rate surpassing 10 5 s −1, solution‐processed organic light‐emitting diodes achieve to date the best external quantum efficiencies at very high brightness (1000–10 000 cd m −2 ) among wet‐processed purely organic electroluminescent devices.